The Potential of Pepper Shell (Piper Nigrum) for Supercapacitor Electrodes - Kurniawan, Widodo Budi; Indriawati, Anisa; Marina, Dewi; Taer, Erman (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
A study has been carried out on supercapacitor electrodes as an electrical energy storage media based on pepper shell activated carbon. The Synthesis is done by mixing the waste carbon pepper shell with an activator HCl with a ratio of 1 : 4. Furthermore, the activated carbon is activated physically by using a pyrolysis temperature of 600 0C. The SEM results indicate that carbon has a porous morphology with a pore size of 24.6 nm which is a mesoporous category. Electrochemical properties are analyzed using cyclic voltammetry (CV). The CV results at the scan rate of 1 mV/s indicate the specific capacitance value generated is 0.45 Fg-1. The results showed that pepper shell waste has the potential to be used as a supercapacitor electrode material